PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Empiris pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Habibi, Masandy Muhammad Rais; Muid, Dul (Diponegoro Journal of Accounting, 2024)
This study aims to examine the effect of good corporate governance on the company's capital structure. Good corporate governance is measured by the size of the board of directors, independent commissioners, institutional ownership, managerial ownership and audit committee, and capital structure is measured by the ROA and ROE. Good corporate governance is a concept based on agency theory which is expected to reduce agency conflicts and optimize company funding.This research is a quantitative research with secondary data taken by documentation technique. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. Samples taken by purposive sampling amounted to 45 companies. The analytical method in this study uses multiple linear regression analysis with the help of the SPSS 25 program.The results of this research indicate that the number of board of directors has a positive effect on financial performance (ROA). Meanwhile, the audit committee has a significant positive effect on financial performance (ROA). Independent commissioners and institutional ownership have no positive and insignificant effect on financial performance (ROA). Managerial ownership has a negative and significant effect on financial performance (ROA). The board of directors, managerial ownership, and audit committee have a positive and significant effect on financial performance (ROE). Independent Commissioners have a negative and significant influence on financial performance (ROE). Institutional ownership does not have a positive effect on financial performance (ROE).